Identification and Functional Characterization of a Microtubule-Associated Protein, GhCLASP2, From Upland Cotton (Gossypium hirsutum L.) - Zhu, Shou-Hong; Xue, Fei; Li, Yan-Jun; Liu, Feng; Zhang, Xin-Yu; Zhao, Lan-Jie; Sun, Yu-Qiang; Zhu, Qian-Hao; Sun, Jie (Frontiers in Plant Science, 2018)
Cytoplasmic linker-associated proteins (CLASPs) are microtubule associated proteins (MAPs) involved in regulation of dynamics of microtubules (MTs) that play an important role in plant growth and development. In this study, we identified cotton CLASP genes and investigated the function of GhCLASP2. GhCLASP2 was mainly expressed in stem and developing fibers, especially in fibers of the secondary cell wall deposition stage. Ectopic expression of GhCLASP2 in Arabidopsis increased the branching number of leaf trichomes and rescued the defective phenotypes of clasp-1. In cotton, overexpression of GhCLASP2 increased fiber strength, probably related to enhanced expression levels of tubulin, cellulose synthase and expansin genes. Suppression of GhCLASP2 caused shorter internodes and semi-dwarfism, abnormal flower stigma, aborted anthers without pollen grains, and sterility. These changed phenotypes were similar to those observed in the Arabidopsis clasp-1 mutant. GhCLASP2 was co-localized with MTs according to transient experiment. These results suggest that GhCLASP2 functions similarly as AtCLASP, acting as a MAP and controlling cotton growth and development by regulating MTs.